Radial excitation states of η and η′ in the chiral quark model - 陈绍娜 平加伦 (Chinese physics C, 2012)
A chiral quark model is applied to calculate the spectra of pseudoscalar mesons η and η . By analyzing the obtained spectra, we find that the mesons η （2 1 S 0 ）, η（4 1 S 0 ）, η （3 1 S 0 ） and η （4 1 S 0 ） are the possible candidates of η（1760）, X（1835）, X（2120） and X（2370）. The strong decay widths of these pseudoscalars to all the possible two-body decay channels are calculated within the framework of the 3 P 0 model. Although the total width of η （21S0 ） is compatible with the BES Collaboration＇s experimental value for η（1760）, the partial decay width to ωω is too small, which is not consistent with the BES result. If X（1835） is interpreted as η（4 1 S 0 ）, the total decay width is compatible with the experimental data, and the main decay modes will be πa 0 （980） and πa 0 （1450）, which needs to be checked experimentally. The assignment of X（2120） and X（2370） to η （31S0 ） and η （41S0 ） is disfavored in the present calculation because of the incompatibility of the decay widths.